2014
DOI: 10.1113/jphysiol.2013.255687
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term hypoxic vasodilation in vivo is mediated by bioactive nitric oxide metabolites, rather than free nitric oxide derived from haemoglobin‐mediated nitrite reduction

Abstract: Short-term hypoxic vasodilation in vivo isr In a short-term rodent model, hypoxaemia was associated with hypotension and lower plasma nitrite levels suggestive of nitrite bioactivation; this was only partially reversed by NO synthase inhibition. Administration of sodium nitrite produced marked vasodilation and increased nitrosylation. Scavenging of NO had little effect.r Early hypoxic vasodilation is mediated by a complex interaction of multiple NO-related species, rather than by NO from haemoglobin-mediated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…Recently, Miljkovic et al (106) showed that H 2 S is a rapid mediator of nitrite reduction by providing reducing equivalents to Fe 3 + , thereby generating both NO and its reduced congener, nitroxyl (HNO). Vasodilation produced by acute hypoxia in mice in vivo appears to be independent of NO production, and it is associated with reduced plasma nitrite concentration and increased RSNOs (174). This is consistent with H 2 S, as the initial hypoxic signal that mediates downstream increases in both H 2 S 2 and HNO as shown in Figure 7.…”
Section: Reactions With No and Related Compoundssupporting
confidence: 70%
“…Recently, Miljkovic et al (106) showed that H 2 S is a rapid mediator of nitrite reduction by providing reducing equivalents to Fe 3 + , thereby generating both NO and its reduced congener, nitroxyl (HNO). Vasodilation produced by acute hypoxia in mice in vivo appears to be independent of NO production, and it is associated with reduced plasma nitrite concentration and increased RSNOs (174). This is consistent with H 2 S, as the initial hypoxic signal that mediates downstream increases in both H 2 S 2 and HNO as shown in Figure 7.…”
Section: Reactions With No and Related Compoundssupporting
confidence: 70%
“…Changes in capillary O 2 supply rate are due in part to upstream changes in arteriolar tone distant from sites where RBC O 2 saturation is lowest (the venular ends of capillary networks) indicating that conducted microvascular responses [ 16 , 25 , 45 ] are integral to microvascular autoregulation. The other important distinctions to be made are: 1) the septic injury in this study does not involve systemic hypoxia, as arterial O 2 saturations were normal; rather, altered functional capillary density and micro-regions within capillary networks with stopped-flow or decreased capillary O 2 supply cause local hypoxia and thus a different mechanism is likely involved than that of hypoxic vasodilation [ 23 , 46 , 52 ]; 2) the skeletal muscle NO environment in this model is known to be due to an upregulation of iNOS [ 2 ]; 3) microvascular derangements exist in the face of hypotensive [ 2 ], “relatively preserved” [ 7 ] and even normotensive blood pressure [ 3 , 4 ] with fluid resuscitation, normal arterial O 2 concentration and cardiac output [ 3 , 4 ]. Thus microvascular dysfunction is apparently independent of mean arterial pressure and may be masked by seemingly normal cardiovascular parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Blood flow into the capillaries is controlled by the upstream arteriolar tone feeding the capillary network. Vasoactive molecules released from the RBC in response to hypoxic conditions, including ATP [ 135 , 136 ], nitric oxide (generated by deoxy-hemoglobin acting as a nitrite reducatse) [ 137 , 138 , 139 ] and nitrosothiols [ 140 ] have been proposed as possible mediators of hypoxic vasodilation; though, the role of nitric oxide vis-à-vis nitrosothiols and reaction with the hemoglobin βCys93 residue is somewhat controversial [ 141 , 142 , 143 ]. As RBCs travel through the microcirculation, ATP may be released in hypoxic regions from ATP compartments [ 144 ] via the RBC Pannexin-1 channel [ 145 ].…”
Section: Sepsis Impairs Rbc O 2 -Dependent Atp mentioning
confidence: 99%